2015
DOI: 10.1121/1.4921674
|View full text |Cite
|
Sign up to set email alerts
|

ViSQOLAudio: An objective audio quality metric for low bitrate codecs

Abstract: Streaming services seek to optimise their use of bandwidth across audio and visual channels to maximise the quality of experience for users. This letter evaluates whether objective quality metrics can predict the audio quality for music encoded at low bitrates by comparing objective predictions with results from listener tests. Three objective metrics were benchmarked: PEAQ, POLQA, and VISQOLAudio. The results demonstrate objective metrics designed for speech quality assessment have a strong potential for qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 11 publications
(15 reference statements)
1
37
0
Order By: Relevance
“…This phenomena has also been observed using objective metrics [8] along with the fact that treatments with imperceptible quality differences are similarly ranked in terms of their predicted quality. As a result, only treatments that are perceptually different from the perspective of the quality model will produce quality estimates with a A number of models exist that can be used to estimate the objective quality of audio and the QoE of a user listening to the audio [9].…”
Section: Content-quality Relationship For Codecssupporting
confidence: 53%
See 2 more Smart Citations
“…This phenomena has also been observed using objective metrics [8] along with the fact that treatments with imperceptible quality differences are similarly ranked in terms of their predicted quality. As a result, only treatments that are perceptually different from the perspective of the quality model will produce quality estimates with a A number of models exist that can be used to estimate the objective quality of audio and the QoE of a user listening to the audio [9].…”
Section: Content-quality Relationship For Codecssupporting
confidence: 53%
“…As a result, only treatments that are perceptually different from the perspective of the quality model will produce quality estimates with a A number of models exist that can be used to estimate the objective quality of audio and the QoE of a user listening to the audio [9]. ViSQOLAudio is a full-reference signal-based objective metric for measuring the quality of audio, where the quality measure is how similar a human subject would rate a reference audio file against a degraded audio file [8]. ViSQOLAudio was selected for use in this research because it has been shown to be accurate at estimating the quality of degraded audio files [8], though we could equally have used another objective metric in this proof-of-concept.…”
Section: Content-quality Relationship For Codecsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of objective models exist that can predict the perceptual audio quality of an encoded audio clip given the encoded clip and its uncompressed equivalent as reference. PEAQ [1], POLQA [2], PEMO-Q [3] and ViSQOLAudio [4] are four such full-reference models. Each of these models have been used previously to rate the quality of encoded fullband audio [3]- [6].…”
Section: Introductionmentioning
confidence: 99%
“…The same set of signal samples, as described in Table 1, was processed using an objective quality metric, called ViSQOLAudio [9]. This algorithm compares the difference between the reference and degraded audio file.…”
Section: Objective Testmentioning
confidence: 99%